OIL SARDINE FISHERY AT KOZHIKODE DURING THE SEASONS 1959-60 to 1962-63 - Prabhu, M S (Indian Journal of Fisheries, 2011)
The oil sardine fishery at Kozhikode showed an upward trend from 1959-60 to 1961-62 followed by a decline in 1962-63. Non-selective gears, namely, Pattenkolli vala, Mathikolli vala, Thattum vala and Nethel vala (all boat-seines) were the main gears which accounted for the major part of the oil sardine landings. Variations in the quarterly and annual catch-per-net and catch-per-unit of effort of the different gears have been discussed. The fishery was confined mostly to the October-December quarter when generally size groups ranging from 105 to 149 mm contributed to the bulk of the landings. From the occurrence and progression of the different modes it was inferred that the fishery is dependent on more than one-year-class every year and that during certain years several broods of the same year-class enter the fishery- Growth among juveniles was observed to be at a higher rate than among the bigger and older size groups. A special feature of the 1961-62 and 1962-63 seasons was the entry on a large scale of smaller size groups ranging from 65 to 85 mm into the fishery during August and September. Although oil sardine shoals occur within the 45 metre region, heavy concentrations were recorded in the 5 to 25 metre area.